The Effect of Health Education of Anemia in Relation with Knowledge of First-Trimester Pregnant Women in PMB Putu Mastiningsih, Abiansemal - Ayu Pramita Aswitami, Ni Gusti; Mirah Yunita Udayani, Ni Putu (STRADA : Jurnal Ilmiah Kesehatan, 2019)
Anemia in pregnancy is the condition in which the level of mother’s hemoglobin is less than 12 gr/dL (Winkjosastro, 2002). According to WHO’s data, the maternal death in developing countries accounts for 40% related to anemia state in pregnancy. Most of the case is caused by iron deficiency and acute bleeding. Prevention of anemia can be done by giving the iron supplement tablets. However, by giving iron tablets alone, is not enough if pregnant women do not have any compliance about how to take it on. Maternal knowledge is known as the influence of that compliance. In order to increase their knowledge about anemia, providing the health education is a pivotal role. Health education in pregnancy care is an effort to influence other people, whether individuals, groups, or communities so that they do what is expected of education actors.